PENERAPAN METODE PEMBELAJARAN TEMAN SEJAWAT (PEER TUTORING) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IVC SD NEGERI 164 PEKANBARU - Lenggogeni, Ade Soraya Lenggogeni Soraya; Antosa, Zariul Antosa; Alim, Jesi Alexander Alim Alexander (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem on this research is the result of students' mathematics learning is still low. The learning process is only centered on the teacher, the teacher uses a language which is difficult to understand the students so that only one-way communication process. This resulted in students' skills tend to be quiet, students are asked a friend who is considered more intelligent. The study is in the form of classroom action research (PTK) with the aim to improve students' mathematics learning outcomes IVC SD Negeri 164 Pekanbaru. The increase in the average student learning outcomes of student learning outcomes before action is 66.9 with classical completeness 47.05% (incomplete). Once applied learning methods peers (peer tutoring) increased student learning outcomes with an average value of 76.3 UH I, a large increase in 14.05% with classical completeness amounted to 64.70% (not completed) and the average UH II 81 , 6 with a big increase from a base score of 21.97% with 79.41% classical completeness (completed). The average percentage of the activity of teachers in the first cycle was 71.87% increased to 82.81% in the second cycle. And the tutorial activity also increased, in the first cycle the average percentage of the activity of the tutorial is a 70.71% increase to 84 , 28% in the second cycle. In addition to the activities of students in each sikusnya also increased, in the first cycle percentage is 66.07% student activity increased by 82.14% in the second cycle. Based on these results, it can be concluded that the application of learning methods peers (peer tutoring) can increase student mathematics learning outcomes fourth grades at SD Negeri164 Pekanbaru. Keywords: Learning Method Peer Tutoring, Student Achivement the Result of Mathemathics Studies